PENERAPAN SISTEM INFORMASI AKUNTANSI PERSEDIAAN BARANG DAGANG PADA MINIMARKET ****** MART BERBASIS SYARIAH CABANG BANGKA BELITUNG - Jarmini Jarmini; Tinggal Purwanto; Reka Meilani (Budgeting: Jurnal Akuntansi Syariah, 2021)
The results showed that the merchandise inventory accounting information system owned by Minimarket ****** Mart was good. Assessment based on: the inventory recording method is in accordance with the theory using physical recording, the inventory valuation method is in accordance with the theory using the FIFO method, the cash sales procedure applied by ****** Mart can be said to be good and is in accordance with the theory where the cash sales procedure starts from the buyer coming to the store to shop and ends with the cashier who provides a payment receipt proof of the transaction, the purchasing procedure implemented by ****** Mart is still not in accordance with the theory this is because the manager still has concurrent duties as part the buyer of goods and the finance department, the documentation used can be said to be in accordance with the theory where it can be seen that purchases, purchase invoices, inventory stock books.